DEVELOPMENT OF A FUNCTIONAL LABORATORY INSTALLATION FOR THE EVALUATION OF REACTION TIME ON LOCAL EMERGENCY SITUATIONS - , Р. І. (Municipal economy of cities. Series: «Economy science», 2018)
The level of transport support for fire and rescue units plays an important role in the process of eliminating various types of local emergencies. Today, the situation with the level of technical support in the fire and rescue divisions of Ukraine as a whole can be considered unsatisfactory. The reason for this is a physically obsolete fleet of technical equipment and a mismatch in the level of technical equipment of divisions with modern requirements. To solve this problem, it is necessary to carry out a technical re-equipment of fire and rescue units, but, unfortunately, the existing methodological base does not allow performing this task effectively. In this work a functional scheme of a laboratory installation and a complex of hardware and software tools were developed that implement a mathematical model for assessing the response time to local emergency situations of emergency rescue units using multifunctional containers, which allows us to investigate the influence on the response time of a number of important factors. The functional scheme of the laboratory installation consists of eight blocks, which are connected by sequential and hierarchical connections. The developed functional scheme of the laboratory installation and the complex of hardware and software allows to assess the response time to local emergency situations of rescue units of settlements at different versions of their operational vehicles, which creates the prerequisites for the use of risk-oriented approach in solving the problem of technical equipment units. In the future, it is planned to develop a method of equipping the rescue service units with special technical means based on the risk-oriented approach. Keywords: local emergency situation, response time, operational vehicle, laboratory installation.